Peristaltic heat transport analysis of carbon nanotubes in a flexible duct due to metachronal waves of cilia. Issue 2 (3rd November 2022) - Abrar, Muhammad Nasir; Uddin, Salah; Shah, Shahreyar; Razzaq, Raheela
Abstract: This study investigates the natural convection peristaltic transport of creeping viscous nanofluid flow in an axisymmetric flexible circular duct within the cilia walls. Moreover, the impact of radially varying magnetic field, internal heating and thermal radiation impact is also taken into consideration. The governing boundary layer equations are transformed into suitable form by introducing the nondimensional variables. Closed form exact solution is obtained for the momentum, energy, and pressure gradient profiles. Graphical illustrations are produced, which reflect the importance of multiple parameters of concern. With an increase in the heat source parameter and solid volume fraction of nanoparticles, the fluid temperature increases effectively. Trapping phenomena with the help of streamlines are also developed for variation in the flow rate and Grashof number. Streamlines shows that an enhancement in the Grashof number inflates the size of bolus. It is perceived that Copper has less heat transfer ability as compared to CNTs. Temperature profile decreases dramatically with enhancement in the radiation parameter for all types of solid nanoparticles considered. Abstract : This study investigates the natural convection peristaltic transport of creeping viscous nanofluid flow in an axisymmetric flexible circular duct within the cilia walls. Moreover, the impact of radially varying magnetic field, internal heating and thermal radiation impact is also taken into consideration. The governing boundary layer equations are transformed into suitable form by introducing the nondimensional variables. Closed form exact solution is obtained for the momentum, energy, and pressure gradient profiles.…